Implantation of Cryopreserved Human Placental Fragments Restores Prooxidant-Antioxidant Balance in Experimental Animals of Late Ontogeny - Prokopyuk, Olga S.; Prokopyuk, Volodymyr Yu.; Pasieshvili, Nana M.; Chyzhevskiy, Viktor V.; Trifonov, Viktor Yu.; Karpenko, Volodymyr G.; Loginova, Olga O. (Problems of Cryobiology and Cryomedicine, 2017)
The studies have shown that animals of late ontogeny had the misbalance in prooxidative-antioxidative system of blood serum, liver and gonads with shift to the proxidant activity. Nevertheless, the implantation of cryopreserved human placenta fragments to experimental animals increased the activity of endogenous antioxidant system and contributed to the correction of pathological changes associated with aging. Analysis of the findings indicated that the restoration processes occurred both at cell and organism levels. The use of cryopreserved placental fragments in pre-senile age led to a gradual diverse correction of senile involutions, and an increased activity of endogenous antioxidant system during their sanogenesis substantiated the perspective of preventive and therapeutic protocols to treat geriatric pathologies. Probl Cryobiol Cryomed 2017; 27(1): 61–70